Lessons from a pilot study of screening for upper tract urothelial cell carcinoma in Lynch Syndrome - Pluke, Kent David (Division of General Surgery, 2022)
Background: Lynch syndrome is a hereditary disorder, with a very high risk of the developing colorectal cancer (CRC) and a predilection to develop other cancers, including upper tract urothelial carcinoma (UTUC) that has an estimated lifetime risk of 0.2-25%, above that of the general population. Our aim was to assess the prevalence of UTUC in a Lynch syndrome cohort undergoing screening for CRC, to determine the need for a UTUC screening program. Methodology: Lynch syndrome patients were screened with urine dipstix for microscopic haematuria. Patients with confirmed microhaematuria were offered urine cytology, microscopy and culture, ultrasound (US) of their upper tracts and flexible cystoscopy. Results: Of the 89 patients screened, 86 had an MLH1 mutation and 2 had an MSH2 mutation. Eleven of the 12 patients who had microscopic haematuria were female. 10 patients had urinary tract infections. One patient had follicular cystitis and another had a simple renal cyst. No patients had hydronephrosis on ultrasound. All urine cytology specimens were negative for malignancy. Conclusion: No cases of UTUC were detected in our cohort during this study. A more rational screening protocol in this group may be to screen patients for UTUC with known MSH2 mutations at an earlier age (over 35).